2011
DOI: 10.1128/iai.00605-10
|View full text |Cite
|
Sign up to set email alerts
|

Antibodies Contribute to Effective Vaccination against Respiratory Infection by Type A Francisella tularensis Strains

Abstract: Pneumonic tularemia is a life-threatening disease caused by inhalation of the highly infectious intracellular bacterium Francisella tularensis. The most serious form of the disease associated with the type A strains can be prevented in experimental animals through vaccination with the attenuated live vaccine strain (LVS). The protection is largely cell mediated, but the contribution of antibodies remains controversial. We addressed this issue in a series of passive immunization studies in Fischer 344 (F344) ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
52
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(55 citation statements)
references
References 46 publications
(53 reference statements)
2
52
1
Order By: Relevance
“…Furthermore, our data implicate a minimal role for IgG and IgM, in protection against pulmonary tularemia. These findings contrast with previous studies in which passive transfer of purified IgG antibodies, specific for F. tularensis LVS, was found to be protective against both systemic (23) and mucosal (14) challenges. Overproduction of protective IgG antibody, as observed in our model, should in theory compensate for the absence of IgA.…”
Section: Discussioncontrasting
confidence: 56%
See 2 more Smart Citations
“…Furthermore, our data implicate a minimal role for IgG and IgM, in protection against pulmonary tularemia. These findings contrast with previous studies in which passive transfer of purified IgG antibodies, specific for F. tularensis LVS, was found to be protective against both systemic (23) and mucosal (14) challenges. Overproduction of protective IgG antibody, as observed in our model, should in theory compensate for the absence of IgA.…”
Section: Discussioncontrasting
confidence: 56%
“…Cell-mediated immunity is generally considered to be essential for immunity against intracellular pathogens, and humoral immunity is thought to have more of an ancillary role. However, significant evidence in the literature indicates an important role of antibodies against F. tularensis LVS infection (13)(14)(15)(16)(17). Moreover, studies from our laboratory have recently reported a synergistic effect of humoral and cellular immune responses in providing sterilizing immunity against respiratory LVS infection (13).…”
Section: F Tularensis Lvs Infection Causes Significant Tissue Patholmentioning
confidence: 95%
See 1 more Smart Citation
“…tularensis replicates intracellularly, and thus the role of humoral immunity against this pathogen has been controversial; however, significant contributions of the humoral response in F. tularensis infection are supported by a growing body of literature (46)(47)(48)(49)(50)(51)(52). The fact that passive administration of LVS-VϩMPL immune sera fully protected mice against challenge with F. tularensis LVS (data not shown) and extended the mean time to death significantly in mice challenged with F. tularensis Schu S4 by the s.c. route, but not by the i.n.…”
Section: Discussionmentioning
confidence: 96%
“…These results nevertheless clearly demonstrated that immune sera contain protective antibodies and their protective effect correlated well with precipitating antibody content [232]. More recently, studies on the passive transfer of immunity against tularemia in prophylactic mode utilizing both (hyper)immune sera as well as monoclonal antibodies have shown that specific antibodies limited manifestation of the disease, thereby facilitating a sterilizing T cell response to resolve the infection [233][234][235][236][237][238]. Moreover, antibodies can also be used in therapeutic mode, especially when given early after infection [193,239].…”
Section: Prophylaxismentioning
confidence: 99%